2016
DOI: 10.1021/acs.iecr.6b01699
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Carbon Nitride/Chitosan Composite for Adsorption and Electrochemical Determination of Mercury in Real Samples

Abstract: In this research, graphitic carbon nitride (g-C 3 N 4 ) was synthesized using pyrolysis of melamine and its phase, morphology, composition, and structure were characterized by using scanning electron microscopy, transmission electron microscopy, X-ray diffraction, energy dispersive analysis of X-rays, and FT-IR spectroscopy. The modification of carbon paste electrode with g-C 3 N 4 /chitosan composite has been performed using the casting method. Experimental results demonstrated the superb adsorptive propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…The detection of elemental C and N (inset of Fig. 1) using energy-dispersive X-ray spectroscopy (EDS) was attributed to the presence of pristine g-C 3 N 4 and CDs [44]. A small peak of elemental O inevitably appeared due to reaction under ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of elemental C and N (inset of Fig. 1) using energy-dispersive X-ray spectroscopy (EDS) was attributed to the presence of pristine g-C 3 N 4 and CDs [44]. A small peak of elemental O inevitably appeared due to reaction under ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The band in the range of 1230–1650 cm −1 corresponded to the stretching of sp 3 C–N and sp 2 C=N in CN heterocycles that exists within the g-C 3 N 4 compound [52]. The sharp peak at 811 cm −1 corresponded to the alkyne C–H bond (trisubstituted) or the breathing mode of the heptazine arrangement [44]. The alkene C=C bond (conjugated) at 1639 cm −1 was due to the connection between heptazine-based g-C 3 N 4 [53].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noticed that the electrochemical analysis of 10 wt % poly(BPE)/g-C 3 N 4 composite for trace metal ions may be attributed to the lone-pair electrons of nitrogen in the g-C 3 N 4 . The report shows that the highly ordered tri-s-triazine units contain many ideal coordination sites and thus metal ions can intercalate into g-C 3 N 4 through the lone-pair electrons of nitrogen [ 26 , 27 , 28 , 29 ]. The combination of poly(BPE) and g-C 3 N 4 not only improved the conduction pathway on the electrode surface, but also produced a strong conjugate effect on them, enhancing the adsorption of metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, more and more attention has been focused on the application of g-C 3 N 4 in the field of electrochemical sensors [ 26 , 27 , 28 ]. It has been reported that metal ions can be absorbed on a g-C 3 N 4 matrix through electrostatic bonding or coordination with several N-atoms in the tri-s-triazine ring [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the modified electrode in this work was compared with other previous works . The proposed GCE/PPy/S‐IIPs electrode shows good analytical results as shown in Table .…”
Section: Resultsmentioning
confidence: 99%